Study on the Water Usage in Office and Laboratory Buildings - Puti Sri Komala; Ansiha Nur; Ridwan; Alya Sausan Nabila (Jurnal Penelitian Pendidikan IPA, 2025)
This study evaluates the efficiency of water usage in the Department of Environmental Engineering at Universitas Andalas (Unand) by analyzing water consumption volume, identifying potential leaks, and comparing the findings with applicable standards for laboratories and offices. A 1.5-inch water meter was installed at the outlet of the rooftop reservoir on the 4th floor to measure water usage volume, and manual attendance devices were used to record the number of water users in the office and laboratory. Leakage testing was performed using the step test method, where water flow was stopped for 16 hours overnight to monitor changes in the water meter readings, with results indicating no leakage. The study found that the highest water consumption was 39.66 L/person/day in the laboratory and 55.06 L/person/day in the office. Water consumption in laboratories was found to be 100-200 L/person/day according to the standard, while water use in offices slightly exceeds the Indonesian National Standard (SNI) 03-7065-2005 of 50 L/person/day. The study recommends implementing water conservation technologies, such as automatic faucets and dual-flush toilet systems, to reduce water consumption and enhance water efficiency.